2013
DOI: 10.1038/nrclinonc.2013.212
|View full text |Cite
|
Sign up to set email alerts
|

The role of primary care in early detection and follow-up of cancer

Abstract: Primary care providers have important roles across the cancer continuum, from encouraging screening and accurate diagnosis to providing care during and after treatment for both the cancer and any comorbid conditions. Evidence shows that higher cancer screening participation rates are associated with greater involvement of primary care. Primary care providers are pivotal in reducing diagnostic delay, particularly in health systems that have long waiting times for outpatient diagnostic services. However, so-call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
184
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(191 citation statements)
references
References 92 publications
4
184
1
2
Order By: Relevance
“…Primary care providers are pivotal in reducing diagnostic delay, particularly in health systems that have long waiting times for outpatient diagnostic services. Several randomized controlled trials have shown primary care-led follow-up care to be equivalent to hospital-led care in terms of patient wellbeing, recurrence rates and survival, and might be less costly [20].…”
Section: Introductionmentioning
confidence: 99%
“…Primary care providers are pivotal in reducing diagnostic delay, particularly in health systems that have long waiting times for outpatient diagnostic services. Several randomized controlled trials have shown primary care-led follow-up care to be equivalent to hospital-led care in terms of patient wellbeing, recurrence rates and survival, and might be less costly [20].…”
Section: Introductionmentioning
confidence: 99%
“…As Emery et al note, there is significant variation in how providers implement referral pathways. 5 Implementation science recognizes that action is needed at an individual level and a system level in order to make a major change to models of care such as those described by Jefford et al in this issue. 8 Useful frameworks for designing change processes include the Knowledge to Action Cycle 9 , the United Kingdom Medical Research Council Complex Interventions Framework 10 and the Theoretical Domains Framework 11 for the assessment of barriers and enablers to change.…”
Section: Understanding and Preparing To Change Models Of Carementioning
confidence: 99%
“…Analyses of breast cancer diagnostic times in Canada have shown a general increase in wait time since the end of the 1990s 7,9 . That increase is attributed to an increased demand for services without a parallel rise in resources.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the diagnostic phase of breast cancer is an anxiety-provoking and stressful experience for the patient and the family 6 . Although published guidelines outline the appropriate diagnostic algorithms for breast cancer, few recommendations have addressed standardizing the timeliness with which such investigations should occur 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation